2020
DOI: 10.1038/s41419-020-2235-4
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2 promotes spermagonial adhesion through modulating MMPs decay via m6A/mRNA pathway

Abstract: As the foundation of male fertility, spermatogenesis is a complicated and highly controlled process. YTHDF2 plays regulatory roles in biological processes through accelerating the degradation of target mRNAs. However, the function of YTHDF2 in spermatogenesis remains elusive. Here, we knocked out Ythdf2 in mouse spermatogonia via CRISPR/ Cas9, and found that depletion of Ythdf2 mainly downregulated the expression of matrix metallopeptidase (MMPs), thus affecting cell adhesion and proliferation. m 6 A-IP-PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Among the 311 genes that were downregulated in the 168 KO (Table S1), 72 are related to extracellular matrix (p<1.35e-06), which is crucial for oocyte 169 fertility. Interestingly, in sperm too, m 6 A regulation of metallopeptidase is mediated by Ythdf2 170 (Huang et al 2020). 171…”
mentioning
confidence: 99%
“…Among the 311 genes that were downregulated in the 168 KO (Table S1), 72 are related to extracellular matrix (p<1.35e-06), which is crucial for oocyte 169 fertility. Interestingly, in sperm too, m 6 A regulation of metallopeptidase is mediated by Ythdf2 170 (Huang et al 2020). 171…”
mentioning
confidence: 99%
“…These reader proteins play a key role in regulating the mRNA metabolism. Previous report showed that YTHDF1 promotes translation by recognizing m6A, and YTHDF2 recognizes mRNA and often leads to mRNA degradation [13]. We found that FTO silencing could promote the appearance of the m6A peak in HOXB13 mRNA but was accompanied by a decrease in the mRNA expression of HOXB13.…”
Section: Fto Removes the M6a Modi Cation In The 3'utr Region Of Hoxb1mentioning
confidence: 47%
“…After YTHDF1 recognizes an m6A modi cation of mRNA, it can accelerate the translation process [12]. When YTHDF2 recognizes an m6A modi cation, it will promote the transportation of mRNA into the p-body, accelerate mRNA degradation, and inhibit protein translation [13]. It has been found that abnormal expression of these proteins exists in various tumors and affects the occurrence and progression of tumors [14].…”
Section: Introductionmentioning
confidence: 99%
“…The insulin-like growth factor 2 mRNA binding protein (IGF2BP) family proteins, including IGF2BP1-3, can recognize m 6 A containing transcripts. IGF2BPs exert their functions via recruiting RNA stabilizers (Huang H. et al, 2018). Eukaryotic initiation factor 3 (EIF3) can facilitate cap-independent translation (Meyer et al, 2015).…”
Section: Alkbh5mentioning
confidence: 99%
“…Moreover, YTHDF2 is also involved in the initation of other biological process. In spermatogenesis, YTHDF2 regulates cell proliferation and adhesion via modulating the m 6 A methylation of MMPs and simultaneously decreasing the overall translational output (Huang T. et al, 2020). Knockdown of YTHDF2 promotes the expression of MAP2K4 and MAP4K4 and activates MAPK and NF-κB signaling pathways, which facilitate the expression of proinflammatory cytokines and exacerbate the inflammatory response in LPS-stimulated RAW 264.7 cells (Yu et al, 2019).…”
Section: Ythdf2mentioning
confidence: 99%